Recent Advances in the Synthesis of Axially Chiral Cycloalkanes - Zhao, Tonglin; Chen, Ling; Yan, Xufei; Xia, Ying (SynOpen)
Axially chiral cycloalkanes have recently emerged as compelling scaffolds with broad utility in asymmetric catalysis and molecular design. This review provides a concise and graphical overview of synthetic strategies for constructing axially chiral cycloalkanesalkylidene-cyclic alkanes. Representative methods summarized include asymmetric allylic substitution, alkene insertion, carbene cross-coupling, carbonyl condensation/reduction, [2+2] cycloaddition, and deracemization. We aim to offer fundamental insights into this emerging field and facilitate future research toward novel chiral frameworks.